Homeward bound: American families in the Cold War era - May, Elaine Tyler (Basic Books, 1988)
In the 1950s, the term "containment" referred to the foreign policy-driven containment of Communism and atomic proliferation. Yet in Homeward Bound May demonstrates that there was also a domestic version of containment where the "sphere of influence" was the home. Within its walls, potentially dangerous social forces might be tamed, securing the fulfilling life to which postwar women and men aspired. Homeward Bound tells the story of domestic containment - how it emerged, how it affected the lives of those who tried to conform to it, and how it unraveled in the wake of the Vietnam era's assault on Cold War culture, when unwed mothers, feminists, and "secular humanists" became the new "enemy." This revised and updated edition includes the latest information on race, the culture wars, and current cultural and political controversies of the post-Cold War era.
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; amériques; approches et analyses; cold war; cours; discipline; division of household labor; division sexuelle du travail; famille; guerre froide; his4443; histoire; histoire des femmes*; histoire du féminisme; histoire et politique; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sociologie; thématiques; travail; travail domestique; états-unis

Une femme - Ernaux, Annie (Gallimard, 1987)
Annie Ernaux s'efforce ici de retrouver les différents visages et la vie de sa mère, morte le 7 avril 1986, au terme d'une maladie qui avait détruit sa mémoire et son intégrité intellectuelle et physique. Elle, si active, si ouverte au monde. Quête de l'existence d'une femme, ouvrière, puis commerçante anxieuse de «tenir son rang» et d'apprendre. Mise au jour, aussi, de l'évolution et de l'ambivalence des sentiments d'une fille pour sa mère : amour, haine, tendresse, culpabilité, et, pour finir, attachement viscéral à la vieille femme diminuée. «Je n'entendrai plus sa voix... J'ai perdu le dernier lien avec le monde dont je suis issue.
Section: 105 pages ; 18 cm.
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; approches et analyses; care; classisme; cours; discipline; europe; famille; france; inégalités; lit301N; littérature; maternité; premier cycle; privilèges; périodes historiques; régions géographiques; systèmes d'oppressions; thématiques; écriture des femmes*

The Traditional Roles of Native Women in Canada and the Impact of Colonization - Brodribb, Somer (The Canadian Journal of Native Studies, 1984)
Recent trends in feminist research indicate a growing interest in the impact of Native women on westward expansion and imperialism. The author suggests that while early European contacts affected the status of women negatively, the views of Native women were seldom recorded during these early contact periods. Recent studies have examined the status and changing roles of Native women from the viewpoints of contemporary Native women. The diversity of their opinions continues to be a part of the contemporary debate on the resilience and resourcefulness of Native women in the past.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; 1970-1979; 1980-1989; amériques; approches et analyses; canada; cours; discipline; famille; féminisme autochtone; histoire et politique; intersectionnalité; mariage; pol4105; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; sociologie; sofia; système colonial; systèmes d'oppressions; thématiques; violences

La Femme gelée - Ernaux, Annie (Gallimard, 1981)
Professeure de trente ans, mariée à un cadre, mère de deux enfants, elle habite un appartement agréable. Pourtant, c'est une femme gelée. C'est-à-dire que, comme des milliers d'autres femmes, elle a senti l'élan, la curiosité, toute une force heureuse présente en elle se figer au fil des jours entre les courses, le dîner à préparer, le bain des enfants, son travail d'enseignante.
Section: 184 pages ; 21 cm
Keywords: 1900-1999; 1970-1979; 1980-1989; approches et analyses; care; corps; corps féminin; cours; discipline; europe; famille; france; justice sociale; lit301N; littérature; maternité; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sexisme; sexualité; systèmes d'oppressions; thématiques; travail; écriture des femmes*